Cutaneous Breast Cancer Metastasis Is Effectively Treated With Intralesional Interleukin-2 and Imiquimod: A Case Report and Brief Literature Review - Drohan, Ashley; Vidovic, Dejan; Barnes, Penelope Jane; Giacomantonio, Carman Anthony; Helyer, Lucy Kathryn (Frontiers in Oncology, 2022)
Breast cancer is the most common non-cutaneous cancer affecting women worldwide and is a major cause of cancer-related morbidity and mortality in females. While many women are diagnosed with early-stage disease, a subset of women may present with isolated cutaneous metastases or recurrent locoregional cutaneous metastatic disease. There is a paucity of evidence for effective treatments for cutaneous breast cancer metastases. Herein, we present a case of hormone receptor negative, HER2 positive cutaneous breast cancer metastasis treated with intralesional IL-2 and topical imiquimod, which was well tolerated with only minor low grade side effects. We also present a brief literature review of immunotherapy for cutaneous breast cancer metastasis to frame the discussion around using minimally invasive local therapies for this disease. Together, this limited data suggests that intralesional IL-2 and imiquimod may be considered as a safe option when treating a patient with cutaneous breast cancer metastases.